Canine Babesiosis among Indian Native Dog Breeds: Molecular Detection and Clinical Investigation - Jaisree, Srinivasan; Sridhar, Ramasamy; Jayanthi, Natarajan; Palavesam, Azhahianambi; Kalaiselvi, Govindan; Ramya, Rajendhiran; Balakrishnan, Govindan; Soundararajan, Chinnaiyan (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Canine babesiosis is a tick-borne disease of canines caused by Babesia canis (large piroplasm) and Babesia gibsoni (small piroplasm).  This study aims to report an outbreak of babesiosis in a Kennel housing 51 dogs of 19 Indian native dog breeds acquired from various  states of India. A comprehensive disease investigation was conducted following sudden death of puppies with haemorrhagic enteritis.  Samples were collected for virology, bacteriology, clinical pathology, and parasitological examination. PCR and RT-PCR was carried out  to identify canine enteric viruses. For the diagnosis of haemoprotozoa (T. evansi, A. platys, E. canis and Babesia spp), PCR targeting VSG,  16srRNA, virB and 18srRNA genes, respectively, was carried out. On clinical examination dogs had severe tick infestation, melena and  blanched conjunctival mucous membrane. The samples were negative for canine enteric viruses and bacteria of etiological significance,  but were positive for B. canis, B. vogeli and B. gibsoni. The dogs were found negative for T. evansi, A. platys and E. canis. The ticks were  identified as Rhipicephalus sanguineus sensu lato (s.l.). Haematological examination showed anaemia, leukocytosis and thrombocytopenia,  while serum biochemistry revealed elevated total protein, albumin, and creatinine. The study confirmed the outbreak due to B. canis,  B. vogeli and B. gibsoni. Despite haematological and biochemical profiles indicating acute babesiosis, the native dogs showed good  survival rate, suggesting their better tolerance against babesiosis than crossbred dogs.
Keywords: Canine babesiosis; Molecular diagnosis; Native dogs; Treatment